Neutropenia in pediatric hematology/oncology practice - E. A. Deordieva; A. Yu. Shcherbina (Онкогематология, 2015)
Acquired neutropenia is one of the most common conditions in pediatric hematology practice. These conditions usually are benign. In contrast, congenital neutropenia are rare conditions, but in the absence of pathogenic therapy can cause fatal complications. Approach to the differential diagnosis and management of these patients are discussed in this review.